VERIFIKASI METODE PENENTUAN KADAR SO3 TERHADAP WAKTU PENGENDAPAN DALAM SEMEN DI PT. SEMEN BATURAJA - Parawansya, osyellah indar; Safaruddin, Safaruddin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Determination of sulfur trioxide (SO3) in cement samples has been carried out. The method used is gravimetric. The aim of this research is to verify the method for determining SO3 levels in Portland cement samples with results showing that this method can be used at PT. Semen Baturaja Tbk, in carrying out routine tests because it has good precision. Method verification parameters include precision and two-way F test using Excel. Determination of precision is carried out by calculating repeatability and reproducibility is measured by calculating the relative standard deviation (RSD and CVHorwitz for the sulfur trioxide (SO3) parameter with test results respectively being 7.71%, 7.66%, 7.64%, 7.70%. F test Two-way results obtained for a deposition time of 30 minutes, namely an Fcount value of 0.12 and an Ftable of 0.23. For a deposition time of 45 minutes the Fcount value was 0.11 and an Ftable of 0.23. And for a deposition time of 60 minutes the Fcount value was 0. .17 and Ftable of 0.23. Where Fcount < Ftable so that H0 is accepted, so that a settling time of 30 minutes, 45 minutes, 60 minutes can replace a settling time of 3 hours in analyzing SO3 levels in Portland cement.